Learning to sail a building: a people-first approach to retrofit - Bill Bordass; Robyn Pender; Katie Steele; Amy Graham (Buildings & Cities)
To decarbonise the built environment, it is widely assumed that ‘fabric-first’ building upgrades are essential. An alternative, people-first approach is proposed that could deliver energy and carbon reductions at scale and speed. The approach begins by re-examining some rarely questioned assumptions around historical practices and building science. Physics and thermal physiology can inform a reassessment of the causes of thermal discomfort, and show why using air temperature alone as a measure of the thermal environment is inherently problematic. Historical sources reveal the forgotten ways people were made more comfortable in the days before space-conditioning. Together, these encourage a deeper examination of how buildings were constructed, maintained and operated prior to the Industrial Revolution. These insights can be harnessed to develop a practical new trajectory for building operation and retrofit. Preliminary results are reported from two ongoing UK field studies. Co-creation workshops and simple environmental monitoring are being used to encourage occupants to learn to ‘sail’ (i.e. passively manage) their own buildings more effectively to support their own needs. It is not yet possible to put numbers on the energy and carbon saved, but these early experiments may encourage professionals and policymakers to give much greater consideration to ‘people-first’ climate action. Policy relevance A common approach to decarbonising buildings is a focus on ‘fabric-first’ retrofits, which tend to be disruptive, carbon-intensive, expensive and will take decades to convert the stock. Feedback is also exposing disappointing savings, and risks to both building fabric and occupant health. This approach often seeks to update buildings to ‘modern’ standards, using models that have proved problematic, and frequently ignoring in-use performance. Conversely, a ‘people-first’ approach can empower occupants to identify what might improve things, trial simple interventions, and make rapid, low-risk alterations to improve their health and thermal comfort. This can draw on and adapt proven, low-cost historical methods. This alternative ‘soft’ approach uses facilitators to help occupants ‘learn to sail’ (i.e. effectively operate) buildings more effectively and sustainably. The insights will also enable any capital measures to be more precisely targeted.